PENGARUH PEMAHAMAN TENTANG KOPERASI, KUALITAS PELAYANAN, DAN MINAT BERORGANISASI MAHASISWA TERHADAP PARTISIPASI ANGGOTA KOPERASI MAHASISWA - Rosdiana Palapessy; Abdoel Bakar; Walipah Walipah (Jurnal Riset Pendidikan Ekonomi, 2017)
This study aims to determine the effect of each of the variables X1, X2, X3, partially or simultaneously to Y. Using descriptive method, type of research ex-post-fact. Samples of 102 members of the University Students' Cooperative Kanjuruhan Malang by using purposive sampling, data collection methods angkeii. Results showed that the X1 to Y has a significant influence amounted to 42.20%. X2 on Y has a significant influence amounted to 24.14%. X3 to Y also has a significant influence amounted to 37.03%. Simultaneous effect of 47.4%.